If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -5(x + 1) = 4 + -3x Reorder the terms: 2 + -5(1 + x) = 4 + -3x 2 + (1 * -5 + x * -5) = 4 + -3x 2 + (-5 + -5x) = 4 + -3x Combine like terms: 2 + -5 = -3 -3 + -5x = 4 + -3x Solving -3 + -5x = 4 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -3 + -5x + 3x = 4 + -3x + 3x Combine like terms: -5x + 3x = -2x -3 + -2x = 4 + -3x + 3x Combine like terms: -3x + 3x = 0 -3 + -2x = 4 + 0 -3 + -2x = 4 Add '3' to each side of the equation. -3 + 3 + -2x = 4 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 4 + 3 -2x = 4 + 3 Combine like terms: 4 + 3 = 7 -2x = 7 Divide each side by '-2'. x = -3.5 Simplifying x = -3.5
| 3x+2(5x-22)=60 | | 12(z+7)=60 | | x/-3+2=-1 | | 7y-3=2(7)+4 | | x-3/2*3=-2 | | 1+2x=36 | | -5+2=10-9x | | (2x/5)+(3/10)-3x=(5x/8)+(27/4) | | 12(2-7)=60 | | (n/3)=9 | | 6-8x=144 | | 9*9+9-12/4 | | 2/5(k+10)=2/3k | | -(2a+2)=90 | | 6y^2-20y+14= | | 6x-(-5)=13 | | 4(-2)+3y=6 | | -8=r/7 | | 2x/5+3/10-3x=5x/8+27/4 | | 75*3= | | 9=30*(-5)+b | | 7x+2=3(1+x)+2 | | 2(18)+2=4x+2 | | n=4500+0.02p | | 2x^3+17x^2+35x= | | 9/3*3+9-4 | | 17-(3x+5)=3x-6 | | -11x+2=144 | | -1/3(4b+1)=5 | | 2(x-1)-7(3x-2)=7(x-4) | | 16-t=53 | | 2x^3+17x^35= |